THE ECOLOGICAL DIMENSION OF CHEMISTRY EDUCATION IN A TECHNICAL UNIVERSITY - Datsenko, Vita (Educological discourse, 2019)
The experience in the implementation of the methodological system of building the eco-chemical knowledge into the practice of the Kharkiv National Automobile and Highway University has been analyzed. The main purpose of this work is to exchange the experience of increasing the efficiency of the eco-chemical knowledge assimilation under the influence of integrating ecological components into the chemical curriculum. The formation of the ecological consciousness of future specialists is addressed through the creation of the chemical education space, which allows, through the nature of the environmental interaction, for guiding students towards solving ecological issues in both theory and practice. The chemical curriculum in the university is based on the specialty and consist of the most important topics and issues necessary for further professional activities. It’s been shown that integrating ecological components into the chemical curriculum – lectures, laboratory and practical sessions – stimulates the ecological thinking of students. The multidimensional observation of ecological objects, solving ecological tasks, and carrying out eco-oriented laboratory sessions raises students’ interest to the addressed issues of their professional activities, increases the motivation to studying chemical subjects and reinforces the learning efficiency of chemical knowledge. Implementing the ecological component into the curriculum plans of the fundamental and profession-oriented chemical subjects and special courses, along with transforming the approach to writing diploma thesis through the development of the ecology-infused topics of diploma thesis facilitated the development of the chemical knowledge for future engineers with technical occupation in Ukrainian technical universities.